Valoración del riesgo de desarrollar diabetes mellitus tipo 2 a través del Test de Findrisk en la población de la parroquia San Sebastián de la cabecera cantonal del cantón Loja. - Cumbicus Calva, Alex José (2017)
Actually the population growth has led society to modify its lifestyle as a means of adaptation, becoming in risk factors for the development of chronic diseases such as Diabetes Mellitus type 2 (DM2), defining it as a metabolic disorder of multiple etiologies, characterized by chronic hyperglycemia and metabolic disorders. The objectives of this research were to determine the 10 years risk for developing DM2. Know the main risk factors. Establish the gender with greater risk of developing DM2. To determine the age at greatest risk of having DM2. To construct a prevention proposal for the population of the parish "San Sebastián" of the cantonal head of Loja. The present study is a descriptive and cross-sectional quantitative study. A sample of 380 inhabitants who met the inclusion criteria was used. It was determined that 28% (n = 106) presented low risk and 6% (n = 24) very high risk, whose main risk factor for developing DM2 is the high abdominal perimeter with 72% (n = 274). The male gender presented low risk with 16% (n = 61), while the female gender was 9% (n = 33) at high risk. In the 35 years old, presented a low risk with 18% (n = 70) and 55-64 years old with a high risk of 9% (n = 33), gradually increasing risk as age increased. Gender, age, and high abdominal perimeter were identified as determinants for the development of DM2 in the population. Key words: Risk Factors, Type 2 Diabetes Mellitus, Findrisk Test